PERBEDAAN TANGGAPAN PEMIRSA LAKI-LAKI DAN PEREMPUAN TERHADAP KISAHAN FILM LAYANGAN PUTUS - Mulianiputri, Sitian Nisa; Abidin, Aslan; Saguni, Suarni Syam (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Differences in Viewer Responses of Men and Women to the Story of the Film Kite Drops. This study aims to describe the responses and factors that cause differences in the responses of male and female viewers to the story of the film Layangan Putus. Data collection was carried out using literature study techniques and questionnaires using the response perspective theory of Hans Robert Jauss. The results of the study show that: (1) the responses of men, especially those who already have a partner or wife, describe more of their complaints because their partners or wives become more suspicious; (2) the responses of female viewers, especially those who are not yet married, describe more caution because they are careful in choosing a partner; and (3) the cause of differences in the responses of male and female viewers is that the horizons of expectations that each man and woman have are different, making it possible for the difference in acceptance of the film Layang Disconnect.